Locally Different Endothelial Nitric Oxide Synthase Protein Levels in Ascending Aortic Aneurysms of Bicuspid and Tricuspid Aortic Valve. (18th June 2012) - Mohamed, Salah A.; Radtke, Arlo; Saraei, Roza; Bullerdiek, Joern; Sorani, Hajar; Nimzyk, Rolf; Karluss, Antje; Sievers, Hans H.; Belge, Gazanfer
Abstract : Aims . Dysregulated expression of the endothelial nitric oxide synthase (eNOS) is observed in aortic aneurysms associated with bicuspid aortic valve (BAV). We determined eNOS protein levels in various areas in ascending aortic aneurysms. Methods and Results . Aneurysmal specimens were collected from 19 patients, 14 with BAV and 5 with tricuspid aortic valve (TAV). ENOS protein levels were measured in the outer curve (convexity), the opposite side (concavity), the distal and above the sinotubular junction (proximal) aneurysm. Cultured aortic cells were treated with NO synthesis inhibitor L-NAME and the amounts of 35 apoptosis-related proteins were determined. In patients with BAV, eNOS levels were significantly lower in the proximal aorta than in the concavity and distal aorta. ENOS protein levels were also lower in the convexity than in the concavity. While the convexity and distal aorta showed similar eNOS protein levels in BAV and TAV patients, levels were higher in TAV proximal aorta. Inhibition of NO synthesis in aneurysmal aortic cells by L-NAME led to a cytosolic increase in the levels of mitochondrial serine protease HTRA2/Omi. Conclusion . ENOS protein levels were varied at different areas of the aneurysmal aorta. The dysregulation of nitric oxide can lead to an increase in proapoptotic HTRA2/Omi.